Tuberculous meningitis without pleocytosis in an immunocompetent patient: a case report - Dr Hassan Kamena Mwana-yile Mwana-yile; Professor Fatima IHBIBANE; Dr Khadija RIDA; Dr Raissa BONGUNGU; Professor Kamal EL Filali MARHOUM (International Journal of Infectious Diseases)
Background: Cerebrospinal fluid (CSF) pleocytosis is an essential requirement for the diagnosis of meningitis. However, the absence of pleocytosis is a diagnostic challenge for clinicians in cases of suspected meningitis and is rare in cases of tuberculous meningitis in immunocompetent patients. Methods: To Report a case of tuberculous meningitis without CSF pleocytosis in an immunocompetent patient. Results: Patient EI, aged 27, with no history of specific pathologies, presented with a meningeal syndrome (headache, vomiting, meningeal stiffness, positive Kerning and Brudzinski), an infectious syndrome (fever 39°C), and signs of basilar involvement (convergent strabismus) associated with a hacking cough with whitish sputum and night sweats, evolving in a context of weight loss for 15 days. Brain MRI revealed multiple sub-centimetric intra-axial supratentorial and sub-tentorial lesions. Cytobacteriological and chemical examination of the cerebrospinal fluid showed a white blood cell count of fewer than three cells/mm3, hyperproteinorachy at 1.54 g/L, and hypoglycorachy at 0.08 g/L. BK PCR in CSF isolated Mycobacterium tuberculosis DNA without rifampicin resistance.Thoracic-abdominal-pelvic CT revealed micronodules in both lung fields, giving a millet-grain appearance, associated with mediastinal adenopathy and osteolytic lesions of the sacroiliac joint. Pulmonary localization was confirmed by sputum Genexpert. HIV-1 and 2 serology and Lupus work-up were negative, and plasma protein electrophoresis did not reveal hypergammaglobulinemia. Antibacillary chemotherapy and bolus corticosteroids were started as a matter of urgency. Cytobacteriological and chemical examination of the CSF from the follow-up lumbar puncture revealed acellular meningitis, with hyperproteinorachia at 1g/L and hypoglycorachia at 0.25 g/L. Discussion: The clinical manifestations of tuberculous meningitis are diverse, encompassing headache, vomiting, meningeal signs, focal deficits, vision loss, cranial nerve paralysis, and elevated intracranial pressure. The sixth cranial nerve is most commonly affected, leading to convergent strabismus.Cytobacteriological and chemical examination of the CSF is essential for the early diagnosis of tuberculous meningitis. It reveals lymphocytic pleocytosis, hyperproteinorachia, and hypoglycorachia.The occurrence of meningitis without pleocytosis is quite common in severely immunocompromised HIV-infected patients with CD4 counts less than 50 cells/ml who have confirmed tuberculous meningitis. Acellular meningitis is also observed in HIV patients with cryptococcal meningitis. In HIV infection, the level of immunosuppression affects the intracerebral inflammatory process, which explains the lack of pleocytosis in tuberculous meningitis or cryptococcal meningitis.Acellular meningitis is rare in bacterial infections but more common in viral infections in immunocompetent individuals.Tuberculous meningitis cases have been observed with atypical low white blood cell counts in the cerebrospinal fluid, even in individuals with healthy immune systems and in areas where the disease is uncommon. This condition is rarely reported in Morocco and the broader African continent Conclusion: The lack of pleocytosis in the CSF should not rule out meningitis in a patient with signs of meningitis.